PENGARUH PERENCANAAN SDM,MANAJEMEN TALENTA DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA PEGAWAI DIREKTORAT PEMBIAYAAN KEMENTERIAN PERTANIAN RI - Tesa Ivana (2022)
This research is a research using quantitative methods which is carried out with the aim of knowing and proving the influence of human resource planning, talent management and knowledge management on employee performance. The object of this research is an employee of the Direktorat Pembiayaan Kementerian Pertanian RI. In this study, data were collected by distributing questionnaires in the form of statements to 42 employees. The method used in sampling is the saturated sample technique. The analysis in this study uses the help of the SmartPLS 3.0 application. And the results of this study can show that HR planning has a positive and significant effect on employee performance by 2,676, talent management has a not significant effect on employee performance by 1,736, and knowledge management on performance is 4,156, as well as HR planning, talent management, and knowledge management. simultaneous effect on employee performance of 48.6 Keywords: HR planning, talent management, knowledge management and employee performance